Labour market developments in Europe 2013 (Luxembourg, 2013)
"In 2012, the unemployment rate in the EU and the euro area continued to climb further until early 2013, reaching values above 11 and 12% respectively. Labour dynamics continued to differ substantially across countries and the patterns of labour market dynamics across the EU further contributed to increasing the already high degree of dispersion of unemployment rates. Activity rates kept being resilient, but ‘discouraged worker effects’ are becoming stronger over time, in particular in the countries characterised by the highest shares of long-term unemployment.